2021
DOI: 10.1136/bmj.n597
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19: Where are we on vaccines and variants?

Abstract: Nearly a year after WHO declared the covid-19 pandemic, Elisabeth Mahase reports on the latest developments in vaccines, variants, and diplomacy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(122 citation statements)
references
References 10 publications
1
114
0
1
Order By: Relevance
“…Moreover, we did not assume the British or South African mutation. Not all vaccines might protect from these variants [22–24]. Also these situations can be accommodated by the model.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we did not assume the British or South African mutation. Not all vaccines might protect from these variants [22–24]. Also these situations can be accommodated by the model.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, data have been published showing that B.1.1.7 differs in some immunologic characteristics compared to "wild-type" SARS-CoV-2. [67][68][69][70][71][72][73][74] SARS-CoV-2 variants with the E484K amino acid replacement are of particular concern in many areas including Brazil, South Africa, India and elsewhere (https://www.cidrap.umn.edu/news-perspective/2021/02/pfizer-moderna-vaccines-may-be-lesseffective-against-b1351-variant, last accessed: May 17, 2021). Consistent with other studies, we identified the E484K change in several genetically distinct lineages of the virus, a finding likely due to convergent evolution, as noted previously by others.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we did not assume the British or South African mutation. Not all vaccines might protect from these variants [22][23][24]. Also these situations can be accommodated by the model.…”
Section: Plos Onementioning
confidence: 99%